Влияние североатлантического колебания на сток рек Беларуси - Данилович, И. О.; Вжезински, Д.; Лопух, П. С.; Некрасова, Л. А. (БГУ, 2007)
The assessment of the impact of the North Atlantic Oscillation on the hydrological regime of rivers in Belarus has been conducted. The correlation between the NAO and monthly, seasonal and annual discharges was studied, the runoff in the opposite stages of the NAO and the intra-annual distribution of the runoff were analysed. = Изучалась связь между североатлантическим колебанием и среднемесячными, сезонными и среднегодовыми расходами рек, рассмотрен сток при разных фазах колебания и внутригодовое распределение стока.